Happy Ever After - Roberts, Nora (New York Berkley Books, 2010)
As the public face of Vows wedding planning company, Parker Brown has an uncanny knack for fulfilling every bride's vision, but she just can't see where her own life is headed, until mechanic Malcolm Kavanaugh helps her retool her priorities and gives her a good reason to risk her heart for something more.
Keywords: Female friendship -- Fiction; Weddings -- Fiction -- Planning; Connecticut -- Fiction; Love stories